PELAKSANAAN WEWENANG KEPALA DESA DALAM MEMBINA KEHIDUPAN MASYRAKAT DESA SIKAKAK KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI TAHUN 2015-2016 - Yengtri Okman; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aims to determine the implementation of the authority of the Village Head in fostering community life in the village of Sikakak Cerenti District Kuantan Singingi Year 2015-2016 and know the obstacles of the implementation of the authority of the Village Head in fostering the life of people in the village of Sikakak Cerenti District Kuantan Singingi Year 2015-2016 . This research uses qualitative research methods with descriptive research type, which can be interpreted as problem-solving process investigated by describing the state of research subjects based on the facts found.This study m enemukan that the authority of the village chief in fostering security, order and peace of the region and of the villagers in the village Sikakak done by building a guard post, where the village chief also participated in the patrol activities. To foster harmony residents, in the village of Sikakak done by sports matches between RW / RT or between the hamlet and others. In the maintenance of peace, dealing with conflicts and mediate in the village Sikakak the parties to the dispute first brought to the Village Head Office, met, and sought solutions. In preserving and developing mutual aid societies, village head open space for people to participate in rural development activities.The conclusion that the implementation of the authority of the village chief in fostering community life in the village Sikakak Cerenti District of Kuantan Singingi Year 2015-2016 has not been maximized. Obstacles to implement the authority of the Village Head in fostering the life of the community in Sikakak Village Cerenti Sub-district Kuantan Singingi Regency 2015-2016 is the lack of community participation in following the deliberations in the village and the difficulty to eliminate the disease of society as the habit of drinking.Keywords: Authority Village Head, Fostering Community Life. .